Taxonomy and phylogeny of Leptosillia cordylinea sp. nov. from China - Senanayake, Indunil C.; Jeewon, Rajesh; Hyde, Kevin D.; Bhat, Jayarama D.; Cheewangkoon, Ratchadawan (Phytotaxa, 2020)
A survey of monocotyledon plant-inhabiting fungi in Guangdong Province, China, revealed a leptosillia-like taxon from living leaves of Cordyline fruticosa in the Shenzhen University garden. Phylogenetic relationships were investigated based on morphology and combined analysis of the ITS, LSU, RPB2, β-tubulin and tef 1–α gene sequence data. Based on ecological, morphological and phylogenetic data, we introduce Leptosillia cordylinea sp. nov. with a description and illustrations. The morphology of other Leptosillia species is reviewed and a taxonomic key is provided.